Golgi Fragmentation in Alzheimer’s Disease - Joshi, Gunjan; Bekier, Michael; Wang, Yanzhuang (Frontiers in Neuroscience, 2015)
The Golgi apparatus is an essential cellular organelle for post-translational modifications, sorting, and trafficking of membrane and secretory proteins. Proper functionality of the Golgi requires the formation of its unique cisternal-stacking morphology. The Golgi structure is disrupted in a variety of neurodegenerative diseases, suggesting a common mechanism and contribution of Golgi defects in neurodegenerative disorders. A recent study on Alzheimer’s disease (AD) revealed that phosphorylation of the Golgi stacking protein GRASP65 disrupts its function in Golgi structure formation, resulting in Golgi fragmentation. Inhibiting GRASP65 phosphorylation restores the Golgi morphology from Aβ-induced fragmentation and reduces Aβ production. Perturbing Golgi structure and function in neurons may directly impact trafficking, processing and sorting of a variety of proteins essential for synaptic and dendritic integrity. Therefore, Golgi defects may ultimately promote the development of AD. In the current review, we focus on the cellular impact of impaired Golgi morphology and its potential relationship to AD disease development.